In Vitro Antioxidant and Cytotoxic Activity of Aum-Ma-Rit Recipe, A Traditional Herbal Drug for Treatment of Gi Cancer: Pharmaceutical Science-Herbal Technology - Sakulchit, Thaneeka; Yahuafai, Jantana; Sudkhaw, Teerawat; Moosigapong, Kotchakorn; Saeloh, Dennapa; Chokpaisarn, Julalak (International Journal of Life Science and Pharma Research, 2022)
Aum-Ma-Rit recipe (R-AMR), a traditional Thai drug, has been recorded for treatment of GI disorders for several decades. It has been clinically applied as a complementary treatment for taking care of colon cancer patients. However, there are no scientific studies to confirm its traditional use. Therefore, this study was aimed to primarily screen biological properties of RAMR on anti-oxidation as well as anticancer against HT-29 human colon cancer. The recipe with and without tamarind as an aqueous adjuvant was extracted using two types of solvents, water and ethanol. Total phenolic and total flavonoid contents of all tested extracts were evaluated. LC-MS/MS was also performed. DPPH, ABTS, FRAP, and ORAC scavenging assays were used to measure an in vitro antioxidant activity and the property of extracts on killing HT-29 human colon cancer cells was investigated using MTT assay. The result revealed that all sample extracts were composed of a huge source of phenolic and flavonoid. RAMR2.2 possessed an intense antioxidant property against DPPH (17.45 ± 0.3 µg/ml), ABTS (4.04 ±0.01 µg/ml), FRAP (6859.26 ± 0.00 µM of FeSO4 equivalent/mg of extract), ORAC (334.06 ± 18.52 µM of trolox equivalent/mg of extract), and also inhibiting lipid peroxidation (88.78 ± 1.11 %). MTT assay revealed that extracts have no cytotoxic effects on HT-29 human colon cancer cells. R-AMR had a strong ability on anti-oxidation even if it had less cytotoxic effects on HT-29. Therefore, the current study exhibited that the recipe may act as a chemopreventive agent for taking care of cancer patients.